On solutions of forward and inverse problem for potential geophysical fields: Gravity inversion for Urals region - Martyshko, P. S.; Ladovskii, I. V.; Byzov, D. D.; Tsidaev, A. G. (AIP conference proceedings, 2019)
This paper describes method of gravity field interpretation, which is based on the stable algorithm of inversion. Stability of the algorithm is ensured by the selection of initial density model and by step-by-step solution of the problem on the correctness set. We obtain stable and meaningful solution of inverse problem by calculation of small additions from the initial model. Algorithm shows efficiency for the restoration of curvilinear layers. Practical example of interpretation of gravity data is provided for gravity data of Urals region.